陸奥湾におけるスケトウダラ卵および仔稚魚の分布と移動 - 高津, 哲也; 高橋, 豊美; 中谷, 敏邦; 前田, 辰昭; 大越, 金蔵 (NIPPON SUISAN GAKKAISHI)
Distribution and movement of walleye pollock Theragra chalcogramma eggs, larvae, and juveniles were investigated in Mutsu Bay from February to July in 1989 and 1990. During February and March, eggs and larvae were mostly found in the mouth part of the bay. In April, larvae and juveniles were widely distributed in the bay, where the water temperature ranged from 7.5 to 10.1℃ and their main food organisms, particularly Pseudocalanus spp., were abundant in the same area. In this period, large-sized juveniles were mainly collected near the bottom in the eastern part of the bay, whereas larvae and small-sized juveniles were concentrated in the shallow waters near the mouth part of the bay. In May, the water temperature at the surface rose to 10.9-12.7℃ and most of the juveniles moved to the bottom of the western and mouth part of the bay. After June, it seems probable that juveniles began to migrate outside of the bay, because of high water temperature and a lack of food organisms in the bay.